Making customized tree-like structures: integrating algorithmic design with digital fabrication - Figueiredo, Bruno (2009)
The ultimate goal of this paper is to contribute for the discussion on the role of digital technologies in architecture, focusing on the convergence of generative design systems with digital fabrication processes for expanding design capabilities. It presents a generative design system of customized tree-like structures for supporting irregular roof surfaces, as an alternative to conventional architectural design processes. It discusses the introduction of an algorithmic and parametric approach to design problems as a methodology for promoting design experimentation and enabling the fabrication of complex design configurations.